2012
DOI: 10.1038/eye.2012.78
|View full text |Cite
|
Sign up to set email alerts
|

Brow ptosis: are we measuring the right thing? The impact of surgery and the correlation of objective and subjective measures with postoperative improvement in quality-of-life

Abstract: Introduction To assess the effect of brow ptosis on visual function and quality-of-life

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 20 publications
0
7
0
Order By: Relevance
“…After 3 months, we recorded eyebrow height 8.46 ± 0.2 mm in point A, 8.40 ± 0.3 mm in point B and 7.25 ± 0.2 mm in point C (Figs. 5,6,7,8). After 6 months, we recorded eyebrow height 7.46 ± 0.2 mm in point A, 8.20 ± 0.2 mm in point B and 7.35 ± 0.2 mm in point C (Table 1).…”
Section: Macroscopic Findingsmentioning
confidence: 96%
See 1 more Smart Citation
“…After 3 months, we recorded eyebrow height 8.46 ± 0.2 mm in point A, 8.40 ± 0.3 mm in point B and 7.25 ± 0.2 mm in point C (Figs. 5,6,7,8). After 6 months, we recorded eyebrow height 7.46 ± 0.2 mm in point A, 8.20 ± 0.2 mm in point B and 7.35 ± 0.2 mm in point C (Table 1).…”
Section: Macroscopic Findingsmentioning
confidence: 96%
“…The perioral and eye are very important for the appearance of patients. The aging of this area is characterized by reduction of the volume and shape, curvature and ptosis which can impair normal peripheral vision [ 7 ]. The eyes together with the mouth have important functions related to facial expressions.…”
Section: Introductionmentioning
confidence: 99%
“…The importance of patient reported outcome measures in healthcare is widely recognised [ 21 , 22 ]. Where studies of ptosis have measured patient reported outcomes, these tend to focus on changes to vision and related functional quality of life [ 18 , 23 , 24 ]. However, studies focusing on changes to health-related quality of life (HRQL) following ptosis surgery indicate long-term benefits [ 12 , 25 ], and recent qualitative work suggests a clear psychosocial benefit of successful ptosis treatment for some patients [ 10 ].…”
Section: Introductionmentioning
confidence: 99%
“…11 Absorbable multipoint fixation devices such as Endotine or Endotine ST (Microaire Corporation, Charlottesville, Virginia) have been used for 15 years to correct cosmetic deformities of the eyebrow and midface. [12][13][14][15][16] However, there are clinical situations that require functional (noncosmetic) repositioning of the forehead, eyebrow, and midface. Examples include obscured visual fields from a mechanical eyebrow ptosis, midface descent or paralysis contributing to lower eyelid retraction, and impairment of upper lip or oral commissure dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…18 Consequently, patients may complain of upper eyelid heaviness and difficulty with peripheral vision, seeing things up high over the forehead, or having to manually elevate the eyelid and eyebrow complex to permit optimal vision. 14,19,20 Moreover, due to prolonged frontalis muscle contraction, patients may complain of tension headaches that are often exacerbated by reading or prolonged computer use. 21 To our knowledge, there are no previous studies investigating the use of bio-absorbable implants in the treatment of functional deficits of the forehead, eyebrow, or midface.…”
Section: Introductionmentioning
confidence: 99%